'Prepackaged symbioses': Propagules on roots of the myco-heterotrophic plant Arachnitis uniflora - Dominguez, Laura Susana (2006)
• Arachnitis uniflora, a myco-heterotrophic plant species, has fleshy tuberous roots colonized by the arbuscular mycorrhizal fungal genus Glomus (Phylum Glomeromycota). These roots produce apical and lateral propagules, both reported here for the first time. The objective of the study was to characterize the ontogeny and structure of the propagules, and to determine their function. • Scanning electron microscopy, laser scanning confocal microscopy and light microscopy were used to study the ontogeny and structure of the propagules. • Propagules developed either from cortical parenchyma cells or from cells immediately beneath the root cap; they developed a shoot meristem and cells in the basal region which were colonized by various fungal structures including hyphae and vesicles. • These propagules may detach from the roots, establishing new plants. © New Phytologist (2005).